VENEZUELAN EQUINE ENCEPHALOMYELITIS IN MAN - Casals, J. (The Rockefeller University Press, 1943)
A filterable agent was isolated from the blood and from washings of the upper respiratory passages of a young laboratory worker during a mild, acute, febrile illness. This agent was identified as a strain of Venezuelan equine encephalomyelitis virus. Circulating specific complement-fixing and neutralizing antibodies not present in sera withdrawn during the acute phase of illness were demonstrated in sera obtained during convalescence. A fellow laboratory worker who became similarly ill simultaneously also developed during convalescence specific circulating antibodies not present prior to illness.